Kajian Etnosains pada Kuliner Khas Lampung Seruit: Integrasi dengan Konsep Biologi SMA - Septina Carolina, Hifni; Liliawati, Winny; Sriyati, Siti (Jurnal Biotek, 2024)
The Lampung community has a traditional food called Seruit, which is commonly eaten during traditional ceremonies, religious events, and family get-togethers. Seruit is a dish consisting of several preparations, such as grilled fish, steamed fish wrapped in banana leaves, and fried fish, combined with fermented durian paste and accompanied by boiled vegetables or fresh, raw vegetables. The objective of this research is to elucidate and analyze the ethnoscience study of traditional Lampung cuisine. It serves as a suitable source of biology learning that aligns with the learning outcomes of the Merdeka Curriculum. This study employs a qualitative approach and utilizes data collection techniques through a literature review and interviews. The analysis technique employed is the Miles and Huberman model, which encompasses the processes of data reduction, display, and verification. According to research, the reconstruction of indigenous knowledge into scientific knowledge in the study of ethno-science in Lampung culinary can apply to biology learning. The study of ethnosciences in Seruit includes biodiversity in Indonesia, benefits of specific species, biotechnological processes, and process diagrams.